HIV and Obesity Comorbidity Increase Interleukin 6 but Not Soluble CD14 or D-Dimer. (15th August 2017) - Taylor, Barbara S.; So-Armah, Kaku; Tate, Janet P.; Marconi, Vincent C.; Koethe, John R.; Bedimo, Roger J.; Butt, Adeel A.; Gibert, Cynthia L.; Goetz, Matthew B.; Rodriguez-Barradas, Maria C.; Womack, Julie A.; Gerschenson, Mariana; et al.
Abstract : Objectives: Obesity prevalence among people living with HIV (HIV+) is rising. HIV and obesity are proinflammatory states, but their combined effect on inflammation (measured by interleukin 6, IL-6), altered coagulation (D-dimer), and monocyte activation (soluble CD14, sCD14) is unknown. We hypothesized inflammation increases when obesity and HIV infection co-occur. Methods: The Veterans Aging Cohort Study survey cohort is a prospective, observational study of predominantly male HIV+ veterans and veterans uninfected with HIV; a subset provided blood samples. Inclusion criteria for this analysis were body mass index ≥ 18.5 kg/m 2 and biomarker measurement. Dependent variables were IL-6, sCD14, and D-dimer quartiles. Obesity/HIV status was the primary predictor. Unadjusted and adjusted logistic regression models were constructed. Results: Data were analyzed for 1477 HIV+ and 823 uninfected participants. Unadjusted median IL-6 levels were significantly higher and sCD14 levels significantly lower in obese/HIV+ compared with nonobese/uninfected ( P <0.01 for both). In adjusted analyses, the odds ratio for increased IL-6 in obese/HIV+ patients was 1.76 (95% confidence interval: 1.18 to 2.47) compared with nonobese/uninfected, and obesity/HIV+ remained associated with lower odds of elevated sCD14. We did not detect a synergistic association of co-occurring HIV and obesity on IL-6 or sCD14 elevation. D-dimer levels did not differ significantly between body mass index/HIV status groups. Conclusions: HIV–obesity comorbidity is associated with elevated IL-6, decreases in sCD14, and no significant difference in D-dimer. These findings are clinically significant, as previous studies associated these biomarkers with mortality. Future studies should assess whether other biomarkers show similar trends and potential mechanisms for unanticipated sCD14 and D-dimer findings. Abstract : Supplemental Digital Content is Available in the Text.